Periodontal Health and Total Antioxidant Capacity for Jordanian Smokers at Dental Teaching Clinic - Noor Al Mortadi; Khaled Al Qudah; Sabha Alshatrat; Karem H. Alzoubi; Rania Mahafdeh (International Journal of Dentistry)
Conclusion: The imbalance between oxidative stress and antioxidant capacity may play a role in the pathogenesis of periodontal disease. Smoking is highly linked to oxidative stress-antioxidant (redox) imbalance, which exacerbates the impact of periodontitis. This leads to significant oxidative damage, noticeable liver and kidney dysfunction, and elevated systemic inflammation.